“Contemplativus In Actione Iustitiae”: The Testimony Of The Murdered Jesuits Of El Salvador (The Macau Ricci Institute Journal, 2020)
On the evening of 15 November 1989, the El Salvadoran army leadership gathered and decided to take out the alleged “heads” of the insurgency (cf. Doggett, 1993). A special commando group was sent to the José Simeón Cañas Central American University (UCA) run by the Jesuits. The soldiers dragged the priests out of their apartment, forced them to lie face down in the grass and shot them at close range. Besides Ignacio Ellacuría, the rector of the university, they were Segundo Montes, Ignacio Martín-Baró, Amando López, Juan Ramón Moreno and Joaquín López y López. The cook Elba Ramos and her daughter Celina had to die because the soldiers had been ordered not to leave any witnesses of the massacre.Why were the six Jesuits and the two women killed? The shortest answer can be read on the gravestone in the university chapel. Here the most important mission of the Jesuit community in our present time is described, as it had been formulated by the 32nd General Congregation in 1975: “What is it to be a Jesuit today? It is to engage, under the standard of the Cross, in the crucial struggle of our time: the struggle for faith and that struggle for justice which it includes.” (General Congregation 32: 1975) With this basic directive the Jesuits wanted to respond to worldwide injustice as the most urgent challenge in our times. Prophetically, however, the General Congregation also predicted: “We will not work for justice without paying a price.” This sentence is also engraved on the tomb slab.The purpose of this paper is to serve as a memorial to the Jesuit martyrs of El Salvador, so that we may be challenged to deepen our understanding of martyrdom and its significance for overcoming our massive indifference to the sufferings of the poor and the marginalized throughout the world.